The ketogenic diet as an intervention to improve the quality of life in patients diagnosed with West Syndrome: A systematic review (Research, Society and Development, 2023)
The present study aims to evaluate the effectiveness of the ketogenic diet in improving the quality of life of patients with West Syndrome, in the control of spasms and convulsions, the benefits of its use alone and as an adjunct to conservative therapies, and its short-term consequences. and long term regarding its tolerance and side effects. This is a Systematic Literature Review of a qualitative nature, with a search strategy for the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Critical Appraisal Skill Program (CASP) methodological evaluation, analyzing a total of 6 articles. The articles were searched in the PubMed and SciELO databases, excluding simple literature reviews. Articles published in the last 10 years (2013-2023) and available in English were included. After a systematic analysis of the studies, it appears that the ketogenic diet is effective in reducing infantile spasms, especially in cases refractory to combined drug treatments. In addition, the side effects and relapses to the condition were lower than in patients who used adrenocorticotropic hormone. The Atkins diet approach has also been successful in stopping spasms. The ketogenic diet was well tolerated, with minimal side effects when combined with Vigabatrin. Side effects included increased triglycerides and ketone body. It is hoped that future studies will continue to highlight the benefits and improvements in the quality of life of patients with West Syndrome.